Inelastic Deformation of the Slochteren Sandstone: Stress‐Strain Relations and Implications for Induced Seismicity in the Groningen Gas Field. Issue 5 (30th May 2019) - Pijnenburg, R. P. J.; Verberne, B. A.; Hangx, S. J. T.; Spiers, C. J.
Abstract: Pore pressure reduction in sandstone reservoirs generally leads to small elastic plus inelastic strains. These small strains (0.1%–1.0% in total) may lead to surface subsidence and induced seismicity. In current geomechanical models, the inelastic component is usually neglected, though its contribution to stress‐strain behavior is poorly constrained. To help bridge this gap, we performed deviatoric and hydrostatic stress cycling experiments on Slochteren sandstone samples from the seismogenic Groningen gas field in the Netherlands. We explored in situ conditions of temperature ( T = 100 °C) and pore fluid chemistry, porosities of 13% to 26% and effective confining pressures (≤320 MPa) and differential stresses (≤135 MPa) covering and exceeding those relevant to producing fields. We show that at all stages of deformation, including those relevant to producing reservoirs, 30%–50% of the total strain measured is inelastic. Microstructural observations suggest that inelastic deformation is largely accommodated by intergranular displacements at small strains of 0.5%–1.0%, with intragranular cracking becoming increasingly important toward higher strains. The small inelastic strains relevant for reservoir compaction can be described by an isotropic, Cam‐clay plasticity model. Applying this model to the depleting Groningen gas field, we show that the in situ horizontal stress evolution is better represented by taking into account combined elastic and inelastic deformation than it is by representing the total deformation behavior using poroelasticity (up to 40% difference). Therefore, inclusion of the inelastic contribution to reservoir compaction has a key role to play in future geomechanical modelling of induced subsidence and seismicity. Key Points: Triaxial tests on gas reservoir sandstone show inelastic deformation (30%–50% of total) at all stages of compression At the small strains relevant to producing reservoirs (<1%), the inelastic part can be described by an isotropic plasticity model Modelling combined elastic plus inelastic deformation predicts more realistic reservoir stress changes than purely poroelastic estimates